Evaluasi Program Pendidikan Islam di MTsN 1 Kota Pariaman - Aulia Gusli, Ramadhoni; Zakir, Supratman; Ilmi, Darul; Gusli, Ramadhona Aulia; Lestari, Kurnia Mira; Akhyar, Muaddyl (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
The evaluation of Islamic education programs is entrusted to the school principal, with the aim of achieving the educational goals desired by the institution. However, leaders often do not understand their evaluation functions and methods. This study aims to examine the implementation of educational program evaluation at MTsN 1 Kota Pariaman. The study specifically focuses on three aspects: the principal's responsibilities and limitations, and the structure of program assessment. The research method used is qualitative, using a descriptive approach. Data collection involved the use of observations, interviews, and literature study. Data analysis involved the process of collecting, reducing, presenting, and drawing conclusions from the data. The research findings show that the principal's main responsibilities in evaluating educational programs are to develop an evaluation program, collect information from various sources, assess the assessment results, implement improvements based on the assessment findings involving teachers, students, parents, and promote a positive perception of evaluation as a means of improvement. Program evaluation takes two different forms: normal evaluation and evaluation based on Islamic principles. Challenges include limited resources, time restrictions, and lack of collaboration with external entities. Abstrak Evaluasi program pendidikan Islam dipercayakan kepada kepala sekolah, dengan tujuan mencapai tujuan pendidikan yang diinginkan oleh lembaga tersebut. Namun, sering kali pemimpin tidak memahami fungsi dan metode evaluasi mereka. Penelitian ini bertujuan untuk memeriksa pelaksanaan evaluasi program pendidikan di MTsN 1 Kota Pariaman. Studi ini secara khusus berfokus pada tiga aspek: tanggung jawab dan batasan kepala sekolah, serta struktur penilaian program. Metode penelitian yang digunakan adalah kualitatif, menggunakan pendekatan deskriptif. Pengumpulan data melibatkan penggunaan observasi, wawancara, dan studi kepustakaan. Analisis data melibatkan proses mengumpulkan, mengurangi, menyajikan, dan menarik kesimpulan dari data. Temuan penelitian menunjukkan bahwa tanggung jawab utama kepala sekolah dalam mengevaluasi program pendidikan adalah untuk mengembangkan program evaluasi, mengumpulkan informasi dari berbagai sumber, menilai hasil penilaian, menerapkan perbaikan berdasarkan temuan penilaian melibatkan guru, siswa, orang tua, dan mempromosikan persepsi positif evaluasi sebagai sarana peningkatan. Evaluasi program mengambil dua bentuk yang berbeda: evaluasi normal dan evaluasi didasarkan pada prinsip-prinsip Islam. Tantangan termasuk keterbatasan sumber daya, pembatasan waktu, dan kurangnya kolaborasi dengan entitas eksternal.